2011
DOI: 10.3109/00365548.2011.582247
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine herd effect

Abstract: Vaccination ideally protects susceptible populations at high risk for complications of the infection. However, vaccines for these subgroups do not always provide sufficient effectiveness. The herd effect or herd immunity is an attractive way to extend vaccine benefits beyond the directly targeted population. It refers to the indirect protection of unvaccinated persons, whereby an increase in the prevalence of immunity by the vaccine prevents circulation of infectious agents in susceptible populations. The herd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 52 publications
(57 reference statements)
0
98
0
12
Order By: Relevance
“…However, rapid influenza virus mutation necessitates annual vaccine reformulation, and current limitations in the speed of vaccine production can prove problematic when novel influenza strains arise (4). Moreover, attitudes toward vaccination in the general population are by no means uniformly positive (5), and vaccination rates in the United States are consequently inadequate to control influenza transmission fully, particularly in high-risk populations (6). Furthermore, around 85% of developing countries have been estimated to have no access to vaccines during influenza pandemics (7).…”
mentioning
confidence: 99%
“…However, rapid influenza virus mutation necessitates annual vaccine reformulation, and current limitations in the speed of vaccine production can prove problematic when novel influenza strains arise (4). Moreover, attitudes toward vaccination in the general population are by no means uniformly positive (5), and vaccination rates in the United States are consequently inadequate to control influenza transmission fully, particularly in high-risk populations (6). Furthermore, around 85% of developing countries have been estimated to have no access to vaccines during influenza pandemics (7).…”
mentioning
confidence: 99%
“…Herd immunity induced by mass or nation-wide vaccination programs is well documented. [52][53][54] Preliminary studies have shown that lamivudine [55][56] and telbivudine 57 during pregnancy may reduce vertical transmission of HBV. Maternal to infant transmission may occur during the antenatal, intrapartum, or postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Pertussis virtually disappeared in the industrialized world during the 1970s and 1980s, and herd immunity was initially observed [25]. Clearly, pertussis vaccination prevents severe illness and reduces infection-and transmission rates but not to the same extent as seen for other vaccine preventable childhood diseases [26,27]. In addition to reducing its incidence, 50-60 years of vaccination either with WCV and/or ACV profoundly changed the epidemiology of pertussis.…”
Section: Resurgence Of Pertussismentioning
confidence: 99%